The Birth of Imperial Race Medicine - Ureczky, Eszter (Hungarian Journal of English and American Studies, 2020)
Book review: Seth, Suman. Difference and Disease: Medicine, Race, and the Eighteenth-Century British Empire. Cambridge: CUP, 2018. 324 pages. ISBN 978-1-108-41830-0. Pbk. £29.99.